Rural Tourism Destination Competitiveness : Hard Measures versus Soft Measures and Moderating Role of Knowledge Sharing - CHIN, CHEE HUA (Universiti Malaysia Sarawak (UNIMAS), 2021)
Within the tourism literature, there has been a growing interest in the notion of destination competitiveness and there is an increasing trend showing more authors have been taking initiatives investigating the concept of destination competitiveness in the rural tourism context. Realising the fact that the tourism sector was one of the world’s largest growth industries before the COVID-19 pandemic, and the relevance of rural tourism post the pandemic, rural tourism activities are therefore seen to play an essential role in contributing towards rural economic and social welfare, and indirectly, to the country’s economic growth. Therefore, in the review of the current relevant literature in tourism and rural tourism destination, gaps of the literature have been identified and a research model was proposed by the researcher. There is a need to examine and identify factors contributing to the enhancement and development of rural tourism destination competitiveness because these critical factors could provide considerable help to the rural tourism industry. This study intends to investigate the impact of hard measures (i.e., destination appeal and tourism infrastructure) and soft measures (i.e., service quality and destination image) on rural tourism destination competitiveness (i.e., sustainable management, destination marketing efforts, as well as a comparative and competitive advantage). Also, knowledge sharing was adopted as the moderator variable to testify its moderating impact in enhancing the relationship among the four predictors to rural tourism destination competitiveness. Three underlying theories were used to underpin the research framework, namely, Competitiveness Theory, Stakeholder Theory and the Social Exchange Theory. This study took place in six of the rural tourism destinations in Sarawak. A quantitative approach and survey questionnaires were used as the research instruments for data collection. 390 rows of data were used, comprising of respondents from both the international and domestic tourists visited the study sites. The WarpPLS (version 6.0) was used to perform the PLS-SEM analysis to assess the research model. The findings of this study show that ten of the direct relationship hypotheses tested were supported. Interestingly, three of the moderating hypotheses were supported as well. Knowledge sharing was found to have a positive moderating impact on service quality and sustainable management. Also, knowledge sharing was found to positively moderated the relationship between service quality to comparative and competitive advantage. Knowledge sharing was found to have a positive moderating impact on destination image to sustainable management. To summarize, this study significantly enhanced both scholars’ and practitioners’ understanding of the impact on both hard (i.e., destination appeal and tourism infrastructure) and soft (i.e., service quality and destination image) measures on the development of rural tourism destination competitiveness (i.e., sustainable management, destination marketing efforts and comparative as well as a competitive advantage) with tourist’s knowledge sharing as the moderators that enhanced the relationship among the predictors and dependent variables. This study provides a basis for future researchers interested in the field of rural tourism studies to further investigate the relationship among the constructs.